2017
DOI: 10.1093/gbe/evx277
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionary Landscape of A-to-I RNA Editome across Metazoan Species

Abstract: Adenosine-to-inosine (A-to-I) editing is widespread across the kingdom Metazoa. However, for the lack of comprehensive analysis in nonmodel animals, the evolutionary history of A-to-I editing remains largely unexplored. Here, we detect high-confidence editing sites using clustering and conservation strategies based on RNA sequencing data alone, without using single-nucleotide polymorphism information or genome sequencing data from the same sample. We thereby unveil the first evolutionary landscape of A-to-I ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 72 publications
(82 reference statements)
1
26
0
Order By: Relevance
“…It was observed that the level of coding editing was generally less than 10% (Tan et al 2017) except for very few events of high editing levels (e.g., the editing site at position 607 of GRIA2 (Sommer et al 1991); or see the summary table in Hung el al. 's study (Hung et al 2018)). Most nonsynonymous editing events cannot fully posttranscriptionally compensate for the deleterious effects of G-to-A genomic mutations.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…It was observed that the level of coding editing was generally less than 10% (Tan et al 2017) except for very few events of high editing levels (e.g., the editing site at position 607 of GRIA2 (Sommer et al 1991); or see the summary table in Hung el al. 's study (Hung et al 2018)). Most nonsynonymous editing events cannot fully posttranscriptionally compensate for the deleterious effects of G-to-A genomic mutations.…”
Section: Discussionmentioning
confidence: 96%
“…Adenosine-to-inosine (A-to-I) RNA editing is a very common mechanism in metazoans (Porath et al 2017a;Porath et al 2017b;Hung et al 2018). It is catalyzed by the protein families of adenosine deaminases acting on RNA (ADAR), which convert adenosine (A) to inosine (I), leading to differences between the RNA products and the corresponding genomic sequences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…al., applied RNA-Seq data from 20 metazoan species (including chicken), to identify high confidence editing sites. In chicken, 94 A-to-G editing sites were reported, which distribution of these sites had not been discussed in different tissues (Hung et al, 2017). Therefore, in spite of the biological importance of RNA editing, a few studies have been performed in chicken, which indicate much more work is needed to identify the extent of this mechanism in this species.…”
Section: Introductionmentioning
confidence: 99%